2000
DOI: 10.1093/humupd/6.4.396
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twinning and IVF/ICSI treatment: a report of 11 cases and review of literature

Abstract: Monozygotic twinning is a relatively rare event in in-vivo conception, being estimated to occur in 0.42% of all births. The underlying mechanism for monozygotic twin formation is the division of the embryo early in its development. Separation of cells may theoretically occur before or after inner cell mass formation. In this analysis we report 11 cases of monozygotic twins resulting from IVF or intracytoplasmic sperm injection (ICSI) treatment cycles performed between 1991 and 1998 at St James's University Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
76
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 0 publications
1
76
2
Order By: Relevance
“…W i th in th e g en er a l p op ul at io n, mo no ch or i on ic monozygotic twins occur at the rate of 1 in 250 pregnancies ( approximately 0.4%) [3]. Several reports state that the overall rate of monozygotic twins in pregnancies involving assisted reproductive technology was 0.84 to 8.9% of all pregnancy [8][9][10][11][12][13][14][15]. Not only assisted reproductive technology, but also ovulation induction induced monozygotic twins [14].…”
Section: Discussionmentioning
confidence: 99%
“…W i th in th e g en er a l p op ul at io n, mo no ch or i on ic monozygotic twins occur at the rate of 1 in 250 pregnancies ( approximately 0.4%) [3]. Several reports state that the overall rate of monozygotic twins in pregnancies involving assisted reproductive technology was 0.84 to 8.9% of all pregnancy [8][9][10][11][12][13][14][15]. Not only assisted reproductive technology, but also ovulation induction induced monozygotic twins [14].…”
Section: Discussionmentioning
confidence: 99%
“…Alikani et al (2003) found MZT in 2.4% of ICSI cycles in contrast to 1.6% in conventional IVF cycles. Abusheika et al (2000) reported that there is a higher incidence of MZT in the group of patients who were treated with ICSI (8.9%) when compared with conventional IVF (0.9%). Knopman et al (2010) found no significant difference in the incidence of MZT (2.0%) in their study group when ICSI was performed in 1410 cycles or IVF in 3039 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…It has been theorised that techniques which manipulate the zona such as ICSI and assisted hatching may cause MZ twins to form due to the construction of an aberrant opening that allows spontaneous herniation of the blastocyst [19]. The zona is considered to act as a barrier that limits the degree in which the inner cell mass can divide and disruption of this barrier may contribute to the twinning process [20]. Knopman et al state that the delayed implantation time seen for blastocyst transfer may contribute to the increased risk whereas Carrillo-Vadillo et al [21] and Franasiak et al [17] declare that the prolonged culture exposure may cause a decline in the integrity of the zona pellucida leading to an increased chance of the embryo dividing due to the herniation of the blastomeres.…”
Section: Discussionmentioning
confidence: 99%